The influence of night length: Activity of the northern bat Eptesicus nilssonii under conditions of continuous light in midnight sun compared to a southern population - Frafjord, Karl (BMC Zoology, 2021)
Background - Nearly all insectivorous bats (Chiroptera) are strictly nocturnal, flying and feeding only between sunset and sunrise despite lower insect availability than by day, most likely to avoid predation by diurnal birds. This may represent a great challenge to bats living north of the Arctic Circle, which are exposed to bright nights in the period of the midnight sun. The northern bat Eptesicus nilssonii was studied at different latitudes in Norway (69, 66 and 58°N) by three techniques; visual counts of exits from and returns to roosts, infrared detection with a datalogger and an ultrasound data recorder, to reveal how their activity varied across latitude, season, and night, as well as across light levels. How does a nocturnal bat adjust to perpetual light and what light levels are tolerated? Results -In the north the bats’ active season lasted 2.5 months, 1.5 months shorter than in the south. The bats only flew in 3-4 weeks of midnight sun, and hardly ever left the roost until the sun went behind a hill in the evening. In addition, the timing of their nightly hunting was highly influenced by the darkness of the sky, and they very rarely flew in light levels above 200 foot-candles (FC). As the night became darker than twilight from early August, the bats restricted their activity to between sunset and sunrise. This was the normal situation in southern Norway, where the bats tracked sunset and sunrise throughout the entire season. Those bats appeared to prefer light levels below 100-50 FC and hence, also did fly in twilight conditions. Conclusions - The willingness to fly in twilight by the southern population may be a prerequisite to the northern bat’s survival in the land of the midnight sun. These bats must accept short nights in the first part of their summer season and must be willing to fly in light levels 2-4 times higher than in the south. Most likely, this depends on a reduced predation risk and good abundance of insects at night.